Alelopati dan Masa Depan Bioherbisida Berbasis Tumbuhan: Pengaruh Genetik dan Lingkungan – Sebuah Tinjauan - Hariy Laksamana; Atika Suri; Indra Purnama (Vegetalika, 2025)
Weeds remain a persistent challenge in agriculture, significantly reducing crop productivity by competing for essential resources such as light, water, and nutrients. Although synthetic herbicides are widely used for weed control, their long-term application raises serious environmental and health concerns. As a sustainable alternative, plant-based bioherbicides that harness allelopathy—the natural chemical interactions among plants—are gaining attention. This review explores recent findings on the allelopathic potential of invasive and native plant species, focusing on key allelochemicals such as flavonoids, phenolics, and terpenoids that exhibit phytotoxic effects on weed species. Genetic factors, including specific quantitative trait loci (QTLs) and metabolic pathways involved in allelochemical production, are also discussed as critical determinants of allelopathic expression. Furthermore, environmental conditions such as temperature, soil composition, and light regimes can influence the efficacy and persistence of allelopathic compounds in the field. Understanding the synergistic interaction between genetics and environmental variables is essential for the development and optimization of effective, eco-friendly bioherbicides. This review highlights the current challenges and prospects in integrating allelopathy into weed management strategies for sustainable agriculture.